Efek proses chemical milling pada al-2024-t3 terhadap perilaku perambatan retak fatik berdasarkan beban lebih tarik tunggal - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Lingkungan Hidup,UGM, 1998)
ABSTRACT The objective of this research is to investigate the effect of the chemical milling product on the characteristic of crack growth rate. The material was Al 2024-T3 sheets, and the chemicals were NaOH and Na2S. The specimens were tested under sinusoidal load with constant amplitude. The crack extension was monitored using two traveling microscopes. A single tension overload was applied manually, after the crack extended to approximately 4 mm. The crack tip was observed with optical microscope and SEM. The experimental results show that the overload significantly decrease the crack growth rate. In addition, the decrease in the chemical milling product is smaller than the base material. The optical microscope photograph shows that the crack tip is blunt and the crack mechanism is transcrystalline.